Modeling Transportation Demand of Urban Households in Tehran Province: (System Wide Approach) - Mehdi Taghavi; Mir Hossein Mosavi (سیاست‌گذاری پیشرفت اقتصادی, 2014)
Transportation services as an important component of the urban economy is one of the items constituting the household portfolios. This paper aims to model the transportation demand among urban households in Tehran by using a system-wide approach to modeling demand. For this purpose, data on household spending in Tehran province, during the period of 1389 to 1358 is used. Results indicate that the demand for transport services have low sensitivity to price changes and price changes have little impact on demand management in this section. Income elasticity of demand for urban households in Tehran province of transport services is equal to 1.59.